论《大长今》中的孝道思想在新加坡本地青年群体中的传播和意义 = Analysis of filial piety ideology in "Dae Jang Geum" and its dissemination and significance among Singapore youth communities - 张菁菁 Zhang, Jingjing (2016)
The pass of time and changes in the society cause the importance of East Asian traditional ideology of filial piety to fade especially in the invasion of western popular culture. Singapore is a country where by majority of the population are Chinese. Despite the pursuit of modernization, retaining and further developing their traditional culture and ideological value is being valued. Instilling the ideology of filial piety brings positive impact in the development of teenagers in Singapore. South Korea, being a country that preserved and developed the ideology of filial piety emphasis of its importance. The popularity of Korean drama serve as a great vessel to spread this ideology and amongst of these dramas is Dae Jang Geum. The show is well liked by Singaporean youths and possess influence upon them. Therefore, to discover the effective channel to instill such ideology within the Singapore youth community, we have to examine the dissemination and significance of Dae Jang Geum series. This thesis will adapt the progressive methodology with relevance to the drama series to assure the completeness and comprehensiveness of this research.